Characterizing the disability experience among adults living with HIV: a structural equation model using the HIV disability questionnaire (HDQ) within the HIV, health and rehabilitation survey - O’Brien, Kelly K. (BMC Infect Dis, 2019)
BACKGROUND: People aging with HIV can experience a variety of health challenges associated with HIV and multimorbidity, referred to as ‘disability’. Our aim was to characterize the disability experience and examine relationships between dimensions of disability among adults living with HIV. METHODS: We performed a structural equation modeling analysis with data from the Canadian web-based HIV, Health and Rehabilitation Survey. We measured disability using the HIV Disability Questionnaire (HDQ), a patient-reported outcome (69 items) that measures presence, severity and episodic features of disability across six domains: 1) physical symptoms, 2) cognitive symptoms, 3) mental-emotional health symptoms, 4) difficulties carrying out day-to-day activities, 5) uncertainty and worrying about the future, and 6) challenges to social inclusion. We used HDQ severity domain scores to represent disability dimensions and developed a structural model to assess relationships between disability dimensions using path analysis. We determined overall model fit with a Root Mean Square Error of Approximation (RMSEA) of < 0.05. We classified path coefficients of ≥ 0.2–0.5 as a medium (moderate) effect and > 0.5 a large (strong) effect. We used Mplus software for the analysis. RESULTS: Of the 941 respondents, most (79%) were men, taking combination antiretroviral medications (90%) and living with two or more simultaneous health conditions (72%). Highest HDQ presence and severity scores were in the uncertainty domain. The measurement model had good overall fit (RMSEA= 0.04). Results from the structural model identified physical symptoms as a strong direct predictor of having difficulties carrying out day-to-day activities (standardized path coefficient: 0.54; p < 0.001) and moderate predictor of having mental-emotional health symptoms (0.24; p < 0.001) and uncertainty (0.36; p < 0.001). Uncertainty was a strong direct predictor of having mental-emotional health symptoms (0.53; p < 0.001) and moderate direct predictor of having challenges to social inclusion (0.38; p < 0.001). The relationship from physical and cognitive symptoms to challenges to social inclusion was mediated by uncertainty, mental-emotional health symptoms, and difficulties carrying out day-to-day activities (total indirect effect from physical: 0.22; from cognitive: 0.18; p < 0.001). CONCLUSIONS: Uncertainty is a principal dimension of disability experienced by adults with HIV. Findings provide a foundation for clinicians and researchers to conceptualize disability and identifying areas to target interventions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-019-4203-0) contains supplementary material, which is available to authorized users.